ANALISIS PERCEPATAN PROYEK MENGGUNAKAN METODE EVALUATION VARIANS AT SCHEDUE DAN EARNED VALUE DENGAN TIME COST TRADE OFF - Jajang Atmaja; Gusri Yaldi; Monika Natalia; Monisa Syahendri; Khairurrajuli (LPPM Universitas Abdurrab, 2025)
The success of construction project is determined by the management of cost, quality, and time. Mismatches between the initial plan and field conditions often cause delays and cost overruns. Project X with a cost of IDR 4,144,190,311.75 with a planned implementation time of 180 days, experienced a delay with a deviation of -10.09% on the 91st day. This study aims to analyze project acceleration to delays solution by implementing the evaluation variance at schedule method, earned value and time cost trade off method. The results of the study using the evaluation variance at schedule method, that the delay manajement index was 0.36, and delay production index was 0,64. This delay caused by delay of material arrivals, low labor productivity, and low skilled workers in project. With the earned value, the estimated project completion time was 215 days, its mean 35 days late with an estimated project completion cost of IDR 4,775,028,805.39. The result time cost trade off method with the addition of work shifts, add cost IDR 780,771,895.34 and total cost is IDR 4,924,962,207.09 and 180 days. With the addition of working hours (overtime), add cost IDR 836,528,250.97 and total cost is IDR 4,980,718.562.72 and 188 days. The addition of work shifts is recommended for delay solution.